Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1039/c5nr00251f
|View full text |Cite
|
Sign up to set email alerts
|

Payload drug vs. nanocarrier biodegradation by myeloperoxidase- and peroxynitrite-mediated oxidations: pharmacokinetic implications

Abstract: With the advancement of nanocarriers for drug delivery into biomedical practice, assessments of drug susceptibility to oxidative degradation by enzymatic mechanisms of inflammatory cells become important. Here, we investigate oxidative degradation of a carbon nanotube-based drug carrier loaded with Doxorubicin. We employed myeloperoxidase-catalysed and peroxynitrite-mediated oxidative conditions to mimic the respiratory burst of neutrophils and macrophages, respectively. In addition, we revealed that the cytos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
(59 reference statements)
0
15
0
Order By: Relevance
“…Notably, not only the nano-carrier, but also the payload (drug) may undergo degradation. In a recent study, we were able to demonstrate that SWCNTs externally functionalized with doxorubicin could be employed for drug delivery, and found that the nano-carriers improved the efficacy of the drug in an in vitro melanoma cell model due to the protection provided against oxidative degradation exerted by MDSC present in the cell culture [168]. Thus, on the basis of these studies, one may conclude that it is crucial to understand and control the degradation of carbon-based nanomaterials, not only from the perspective of their perceived toxicity, but also for the implementation of carbon-based drug delivery vehicles.…”
Section: Biodegradation Of Carbon-based Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, not only the nano-carrier, but also the payload (drug) may undergo degradation. In a recent study, we were able to demonstrate that SWCNTs externally functionalized with doxorubicin could be employed for drug delivery, and found that the nano-carriers improved the efficacy of the drug in an in vitro melanoma cell model due to the protection provided against oxidative degradation exerted by MDSC present in the cell culture [168]. Thus, on the basis of these studies, one may conclude that it is crucial to understand and control the degradation of carbon-based nanomaterials, not only from the perspective of their perceived toxicity, but also for the implementation of carbon-based drug delivery vehicles.…”
Section: Biodegradation Of Carbon-based Nanomaterialsmentioning
confidence: 99%
“…Thus, on the basis of these studies, one may conclude that it is crucial to understand and control the degradation of carbon-based nanomaterials, not only from the perspective of their perceived toxicity, but also for the implementation of carbon-based drug delivery vehicles. Indeed, it is important to strike the right balance between degradation and resistance of the carrier and its payload against oxidants generated by inflammatory cells in the tumor microenvironment [168]. …”
Section: Biodegradation Of Carbon-based Nanomaterialsmentioning
confidence: 99%
“…Interestingly, besides heat-mediated tumor ablation, this treatment resulted in a potent CD8+ T-cell–dependent response against the tumor, preventing the recurrence of tumor growth (Toraya-Brown et al, 2014). Another study demonstrated that tumor-associated myeloid-derived suppressor cells (MDSCs) characterized by high levels of oxidative reactions may be responsible for the degradation of chemotherapeutic drugs in the tumor environment, and that this degradation could be significantly reduced by drug loading onto functionalized carbon nanotubes (Seo et al, 2015). This example offers an effective way to prolong drug function in the tumor environment by using a nanodelivery approach.…”
Section: Achievementsmentioning
confidence: 99%
“…Interestingly, besides heat-mediated tumor ablation, this treatment resulted in a potent CD8+ T-cell-dependent response against the tumor, preventing the recurrence of tumor growth (Toraya-Brown et al, 2014). Another study demonstrated that tumor-associated myeloid-derived suppressor cells (MDSCs) characterized by high levels of oxidative reactions may be responsible for the degradation of chemotherapeutic drugs in the tumor environment, and that this degradation could be significantly reduced by drug loading onto functionalized carbon nanotubes (Seo et al, 2015). This example offers an effective way to prolong drug function in the tumor environment by using a nanodelivery approach.…”
Section: Application Of Nanoparticles For Cancer Immunotherapymentioning
confidence: 99%